Islamic Parenting Challenges and Strategies in the Digital Era: Modern Islamic Parenting and School of Parenting - Fitriyah, Salsabila Bil; Maksum, Moh. Nur Rochim (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2023)
The rapid development of digital technology propagates to every level of the environment, one of the smallest is the family environment. Many consider Islamic parenting to be no longer applicable. this is due to the lack of a positive image of Islamic parenting activities. This research is literature or study literature, which contains theories related to the problems in this study. Islamic parenting means a pattern of parenting in which in the parenting process, children grow and develop in accordance with Islamic values that rely on the Quran and As-Sunnah. Childcare is carried out according to Islamic religious guidance. Educating children according to the times, does not mean educating children according to world trends. But prepare children to survive in their time by staying true to the truth. The description of challenges is written based on existing data, and strategies are written based on the book "Modern Islamic Parenting" and the application "School of Parenting".